The Tonal Inertia: Contemporary Music in Music Education (2023)
The present article presents a survey of the main works in Spanish language that concerns contemporary music in the educational context in Spain. The main concern of these works is the absence of contemporary repertoire in the educational processes. This reveals in some way an outdatedness with respect to contemporary musical practices, and make us inquire about the reason for this situation and how to correct it. Additionally, this relationship is discussed from the point of view of both the teachers, who are the first accountable in music education, and the students. On the other hand, some examples are presented where this music has been implemented in classrooms. These are positive cases of aesthetic openness that aim at developing a critical sense and attitude in the students, as opposed to the perspective of the tonal system that seems to search only for the development of technical skills within the system itself.